Structural organization of dream experience during daytime sleep-onset rapid eye movement period sleep of patients with narcolepsy type 1. Issue 8 (14th February 2020) - Cipolli, Carlo; Pizza, Fabio; Bellucci, Claudia; Mazzetti, Michela; Tuozzi, Giovanni; Vandi, Stefano; Plazzi, Giuseppe
Abstract: Study Objective: To assess the frequency of dream experience (DE) developed during naps at Multiple Sleep Latency Test (MSLT) by patients with narcolepsy type 1 (NT1) and establish, using story-grammar analysis, the structural organization of DEs developed during naps with sleep onset rapid eye movement (REM) period (SOREMP) sleep compared with their DEs during early- and late-night REM sleep. Methods: Thirty drug-free cognitively intact adult NT1 patients were asked to report DE developed during each MSLT nap. Ten NT1 patients also spent voluntarily a supplementary night being awakened during the first-cycle and third-cycle REM sleep. Patients provided dream reports, white dreams, and no dreams, whose frequencies were matched in naps with SOREMP versus non-REM (NREM) sleep. All dream reports were then analyzed using story-grammar rules. Results: DE was recalled in detail (dream report) by NT1 patients after 75% of naps with SOREMP sleep and after 25% of naps with NREM sleep. Dream reports were provided by 8 out of 10 NT1 patients after both awakenings from nighttime REM sleep. Story-grammar analysis of dream reports showed that SOREMP-DEs are organized as hierarchically ordered sequences of events (so-called dream-stories), which are longer and more complex in the first and fourth SOREMP naps and are comparable with nighttime REM-DEs. Conclusions: The similar structural organization of SOREMP-DEs with nighttime REM-DEs indicates that their underlying cognitive processes are highly, albeit not uniformly, effective during daytime SOREMP sleep. Given the peculiar neurophysiology of SOREMP sleep, investigating SOREMP-DEs may cast further light on the relationships between the neurophysiological and psychological processes involved in REM-dreaming.